2022
DOI: 10.1080/16549716.2022.2090100
|View full text |Cite
|
Sign up to set email alerts
|

Improving disease surveillance data analysis, interpretation, and use at the district level in Tanzania

Abstract: An effective disease surveillance system is critical for early detection and response to disease epidemics. This study aimed to assess the capacity to manage and utilize disease surveillance data and implement an intervention to improve data analysis and use at the district level in Tanzania. Mapping, in-depth interview and desk review were employed for data collection in Ilala and Kinondoni districts in Tanzania. Interviews were conducted with members of the council health management teams (CHMT) to assess at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… 25 26 One suggestion to help team members realise the value and importance of their work was to increase engagement through training opportunities. 27 28 However, it has been argued that training alone is insufficient to build this awareness, and it must be coupled with efforts to hold regular meetings, data reviews and mentoring opportunities in the use of data in decision-making to successfully engage workers so that the value of data and their input is demonstrated to them. 29 For NutriDash, the data generated can only be as good as the national nutrition data generated at the country level and challenges remain that may prohibit collection and reporting of essential nutrition data via NutriDash in certain countries or contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 26 One suggestion to help team members realise the value and importance of their work was to increase engagement through training opportunities. 27 28 However, it has been argued that training alone is insufficient to build this awareness, and it must be coupled with efforts to hold regular meetings, data reviews and mentoring opportunities in the use of data in decision-making to successfully engage workers so that the value of data and their input is demonstrated to them. 29 For NutriDash, the data generated can only be as good as the national nutrition data generated at the country level and challenges remain that may prohibit collection and reporting of essential nutrition data via NutriDash in certain countries or contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that increased awareness of the importance of timeliness could help with reducing any reporting delays from those responsible for inputting data which in turn, would increase data quality 25 26. One suggestion to help team members realise the value and importance of their work was to increase engagement through training opportunities 27 28. However, it has been argued that training alone is insufficient to build this awareness, and it must be coupled with efforts to hold regular meetings, data reviews and mentoring opportunities in the use of data in decision-making to successfully engage workers so that the value of data and their input is demonstrated to them 29.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated and assessed the status of digital health technologies application for integrated disease surveillance and response in SSA (Karimuribo et al 2012;Mremi et al 2022;Mwabukusi et al 2014). There is evidence of improved early detection and timely response in some cases, whereas other studies found weak and ineffective surveillance systems to control potential infectious disease outbreaks.…”
Section: Digital Technologies and Disease Surveillance And Response I...mentioning
confidence: 99%
“…However, what the study reveals is that as data aggregation increases over time, it is critical to scale up and use advanced techniques such as big data analytics to predict threats and prescribe appropriate responses. Mremi et al (2022) examined the attitudes and practices of members of Tanzania's Council Health Management Teams (CHMT) regarding their capacity to use disease surveillance data in the implementation of a data analysis intervention.…”
Section: Digital Technologies and Disease Surveillance And Response I...mentioning
confidence: 99%
See 1 more Smart Citation